Under a not so white sky: visual impacts of stratospheric aerosol injection - Ansar Lemon; David W Keith; Steve Albers (Environmental Research Letters)
Stratospheric aerosol injection (SAI) could change the sky’s appearance. This could play a role in shaping public perception of SAI. Noticeability depends strongly on tropospheric aerosol optical depth (AOD) and the amount of SAI used. We aim to quantify the noticeability of changes in sky color and brightness due to SAI. We use a 3D visible light radiative transfer package to generate cloudless sky images during high sun, sunset, and twilight under SAI from the reference point of a ground observer. We consider three aerosol types: H _2 SO _4 , CaCO _3 , and diamond. We consider stratospheric aerosol loadings required to produce radiative forcings of −1, −2, and −4 W m ^−2 . We use population density and AOD data to compute the distribution of AODs people experience and then simulate sky images for the 10th, 50th, and 90th percentiles of that distribution. We compare the simulated changes in color and brightness to experimental measurements of minimum thresholds humans can detect. The three aerosol types cause similar changes, except most notably the diamond aerosol increases brightness of the solar aureole by roughly three to five times less than do H _2 SO _4 or CaCO _3 . During high sun, sky whitening from sulfate SAI at −2 W m ^−2 is undetectable for roughly half of observers chosen randomly from the global population. For the remainder of the population, we expect whitening to still be unnoticeable for all but perhaps the most astute observers aided by color samples. Brightening and enlargement of the solar aureole is the most visible feature during high sun for H _2 SO _4 and CaCO _3 , while changes near twilight would be the most noticeable impact of SAI. We cannot evaluate the fraction of the population who would notice these changes.